Surface polishing method of perovskite crystal material and perovskite crystal material
Through the combined treatment of thermal inlay and specific polishing liquid, the surface defect of perovskite single crystal is solved, efficient chemical passivation and nano-scale polishing are achieved, and the photoelectric performance of perovskite single crystal is improved.
Patent Information
- Application Number
- CN202510538136.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2025-07-11
- Estimated Expiration
- 2045-04-27
AI Technical Summary
Traditional polishing methods are difficult to effectively remove micro scratches and defects on the surface of perovskite single crystals, resulting in an increase in carrier recombination and reducing device efficiency and stability.
After using thermal inlay treatment, a combination of artificial leather polishing cloth and anhydrous ethanol and a combination of dimethyl sulfoxide and anhydrous ethanol suspension were used to perform coarse and fine grinding to achieve chemical passivation and nano-scale roughness polishing.
The surface roughness of perovskite single crystals is reduced, surface defects are reduced, crystal transmittance and electrical stability are improved, and photoelectric performance is improved.
Smart Images

Figure CN120287116A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of nuclear radiation detectors, particularly to the surface polishing and treatment technology of semiconductor perovskite materials. More specifically, it relates to a surface polishing method for perovskite crystal materials and perovskite crystal materials. Background Art
[0002] Perovskite single crystals are widely used in fields such as photovoltaic devices, photodetectors, and lasers due to their excellent properties in terms of photoelectric conversion efficiency, stability, and adjustable bandgap.
[0003] The surface quality of perovskite single crystals has a direct impact on their optoelectronic properties. Due to their high brittleness, cracks and fissures are prone to occur. However, traditional polishing methods usually rely on hard abrasive particles such as diamond and alumina for treatment. However, this method is prone to generating micro-scratches on the crystal surface during polishing and is difficult to completely remove, thus forming defects on the crystal surface. These surface defects will become non-radiative recombination centers, thereby leading to an increase in carrier recombination and reducing the efficiency and stability of the device.
[0004] It should be noted that the above information disclosed in this part is only used for the understanding of the background of the inventive concept of the present disclosure. Therefore, the above information may include information that does not constitute prior art. Summary of the Invention
[0005] In view of this, the present disclosure provides a surface polishing method for perovskite crystal materials and perovskite crystal materials, aiming to achieve chemical passivation of the crystal surface while polishing, reduce surface roughness, reduce surface defects, and improve crystal transmittance and electrical stability.
[0006] One aspect of the present disclosure provides a surface polishing method for perovskite crystal materials, including: performing hot embedding treatment on the perovskite single crystal to be polished to obtain a perovskite single crystal sample; fixing the perovskite single crystal sample on a polishing table and performing rough grinding and polishing on the perovskite single crystal sample; and performing fine grinding and polishing on the perovskite single crystal sample after rough grinding to obtain a polished perovskite single crystal sample, wherein the process of fine grinding and polishing includes: using artificial leather polishing cloth and performing a first dropping treatment with absolute ethanol as the polishing liquid; after a preset time interval from the first dropping treatment, replacing absolute ethanol with a suspension of dimethyl sulfoxide and absolute ethanol for a second dropping treatment.
[0007] According to an embodiment of the present disclosure, in the suspension of dimethyl sulfoxide and absolute ethanol, the volume ratio of dimethyl sulfoxide to absolute ethanol is 1:1 - 3:1.
[0008] According to an embodiment of the present disclosure, the hot embedding process specifically includes: using paraffin to perform hot embedding on the perovskite single crystal to be polished to obtain the perovskite single crystal sample, wherein the size of the perovskite single crystal sample obtained by hot embedding is adapted to the size of the sample fixing table on the polishing table.
[0009] According to an embodiment of the present disclosure, the perovskite single crystal sample is successively coarsely ground and polished using silicon carbide sandpapers with mesh numbers in the ranges of 300 - 500, 700 - 900, 1000 - 1300, and 1800 - 2200.
[0010] According to an embodiment of the present disclosure, the sample fixing pressure during the coarse grinding and polishing process is set to 0.1 - 0.2 MPa, the rotation speed of the upper turntable on the polishing table is set to 40 - 60 rpm, the rotation speed of the lower turntable on the polishing table is set to 70 - 90 rpm, and the coarse grinding and polishing time for silicon carbide sandpapers with different mesh numbers is set to 2 - 5 min.
[0011] According to an embodiment of the present disclosure, during the coarse grinding and polishing process, anhydrous ethanol is used for the third dropping treatment, and the flow rate of the third dropping treatment is set to 8 - 20 mL / min.
[0012] According to an embodiment of the present disclosure, after the coarse grinding process is completed, the silicon carbide sandpaper is replaced with artificial leather polishing cloth, and the fiber diameter of the artificial leather polishing cloth is less than 1 µm.
[0013] According to an embodiment of the present disclosure, the artificial leather polishing cloth is composed of polyurethane resin and viscose fiber.
[0014] According to an embodiment of the present disclosure, the sample fixing pressure during the fine grinding and polishing process is set to 0.3 - 0.4 MPa, the flow rate of the first dropping treatment is set to 10 - 30 mL / min, the rotation speed of the upper turntable on the polishing table is set to 40 - 60 rpm, the rotation speed of the lower turntable on the polishing table is set to 80 - 150 rpm, and the preset time interval of the first dropping treatment is set to 20 - 40 min.
[0015] According to an embodiment of the present disclosure, the flow rate of the second dropping treatment is set to 8 - 20 mL / min, the rotation speed of the upper turntable on the polishing table is set to 40 - 60 rpm, the rotation speed of the lower turntable on the polishing table is set to 80 - 150 rpm, and the time of the second dropping treatment is set to 4 - 7 min.
[0016] According to an embodiment of the present disclosure, the purity of the anhydrous ethanol is greater than or equal to 99.99%.
[0017] Another aspect of the present disclosure provides a perovskite crystal, and the surface of the perovskite crystal is processed by using the surface polishing method of the above-mentioned perovskite crystal material.
[0018] According to an embodiment of the present disclosure, by using artificial leather polishing cloth, anhydrous ethanol, and a suspension of dimethyl sulfoxide and anhydrous ethanol for dropping treatment during the fine grinding and polishing process, chemical passivation of the crystal surface can be achieved while polishing, reducing surface roughness, reducing surface defects, and improving crystal transmittance and electrical stability. The present disclosure achieves nanoscale roughness polishing under the condition of not containing abrasive particles such as diamond oxide by using a specific artificial leather polishing cloth, ethanol, and a polishing liquid configured with ethanol and dimethyl sulfoxide. At the same time, dimethyl sulfoxide can dissolve the dangling bonds on the surface of the single crystal, passivate the crystal surface, effectively reduce the dark current of the single crystal, and improve the detection performance of the single crystal. Brief Description of the Drawings
[0019] Through the following description of the embodiments of the present disclosure with reference to the drawings, the above and other objects, features, and advantages of the present disclosure will become clearer. In the drawings:
[0020] Figure 1 Schematically shows a flowchart of a method for surface polishing of a perovskite crystal material according to an embodiment of the present disclosure;
[0021] Figure 2 Schematically shows a comparison diagram of the morphology and transparency samples before and after polishing according to an embodiment of the present disclosure;
[0022] Figure 3 Schematically shows a test result diagram of the roughness of a perovskite crystal of a sample before and after polishing according to an embodiment of the present disclosure;
[0023] Figures 4A to 4C Schematically shows an I-V curve and a laser response result diagram of a sample before and after polishing according to an embodiment of the present disclosure, where Figure 4A is the I-V curve of the unpolished sample; Figure 4B is the I-V curve and laser response of the sample after the first dropping treatment; Figure 4C is the I-V curve and laser response of the sample after the second dropping treatment. Detailed Embodiments
[0024] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. However, it should be understood that these descriptions are merely exemplary and are not intended to limit the scope of the present disclosure. In the following detailed description, for the sake of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure. However, obviously, one or more embodiments can also be implemented without these specific details. In addition, in the following description, descriptions of well-known structures and technologies are omitted to avoid unnecessarily confusing the concepts of the present disclosure.
[0025] The terms used herein are for describing specific embodiments only and are not intended to limit the present disclosure. Terms such as "comprising" and "including" used herein indicate the presence of the described features, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, or components.
[0026] All terms used herein (including technical and scientific terms) have the meanings commonly understood by those skilled in the art, unless otherwise defined. It should be noted that the terms used herein should be interpreted to have a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.
[0027] In cases where expressions similar to "at least one of A, B, and C, etc." are used, generally, it should be interpreted according to the meaning commonly understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include, but is not limited to, a system having only A, only B, only C, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.).
[0028] Perovskite single crystals, especially cesium lead bromide perovskite single crystals, have shown great potential in application fields such as solar cells, photodetectors, and light-emitting diodes due to their unique electronic and optical properties, such as high carrier mobility, long carrier lifetime, and wide bandgap. However, the surface quality of perovskite single crystals directly affects their optoelectronic performance. Surface defects usually become non-radiative recombination centers, leading to increased carrier recombination and reducing the efficiency and stability of devices. Therefore, optimizing the surface treatment method of perovskite single crystals, reducing surface defects, and improving surface quality are crucial for enhancing their performance in optoelectronic devices.
[0029] The applicant has found through research that traditional polishing methods usually rely on hard abrasive particles such as diamond and alumina for treatment, but these methods have certain limitations. Hard particles such as diamond and alumina are likely to leave micro-scratches on the surface of perovskite single crystals, and these scratches are difficult to completely remove, resulting in the generation of surface defects. These surface defects not only affect the optoelectronic performance of perovskite single crystals but may also cause stability problems during long-term use. In addition, traditional polishing methods may also cause damage to the crystal surface structure, especially the impact on the dangling bonds on the crystal surface, which may exacerbate the dark current of the material and thus affect the detection performance.
[0030] The applicant has also found through research that some existing technologies use a form of polishing cloth, polishing liquid, and mechanical polishing machine for polishing. Although this can further improve the surface smoothness, the pressure and heat applied during mechanical polishing may cause uneven treatment on the surface of perovskite single crystals. Especially in the absence of chemical passivation, it may have an adverse impact on the surface, such as stress concentration or a decrease in electrical properties.
[0031] Based on this, embodiments of the present disclosure provide a surface polishing method for perovskite crystal materials, including: performing hot mounting treatment on a perovskite single crystal to be polished to obtain a perovskite single crystal sample; fixing the perovskite single crystal sample on a polishing table and performing rough grinding and polishing on the perovskite single crystal sample; and performing fine grinding and polishing on the perovskite single crystal sample after rough grinding to obtain a polished perovskite single crystal sample, wherein the process of fine grinding and polishing includes: using an artificial leather polishing cloth and performing a first dropping treatment with absolute ethanol as a polishing liquid; after a preset time interval has elapsed from the first dropping treatment, replacing absolute ethanol with a suspension of dimethyl sulfoxide and absolute ethanol for a second dropping treatment. In this embodiment, by using an artificial leather polishing cloth, absolute ethanol, and a suspension of dimethyl sulfoxide and absolute ethanol for dropping treatment during the fine grinding and polishing process, chemical passivation of the crystal surface can be achieved while polishing, reducing surface roughness, reducing surface defects, and improving crystal transmittance and electrical stability. The present disclosure achieves nano-scale roughness polishing without abrasive particles such as diamond oxides by using a specific artificial leather polishing cloth, ethanol, and a polishing liquid configured with ethanol and dimethyl sulfoxide. At the same time, dimethyl sulfoxide can also dissolve the dangling bonds on the surface of the single crystal, perform passivation treatment on the crystal surface, effectively reduce the dark current of the single crystal, and improve the detection performance of the single crystal.
[0032] More advantageously, the above embodiments of the present disclosure provide an environmentally friendly and low-cost polishing process, which can reduce the impact on the environment and operators while ensuring good performance. Different from traditional chemical polishing liquids, the present disclosure uses environmentally friendly solvents such as ethanol and dimethyl sulfoxide and combines an artificial leather polishing cloth for polishing, avoiding the use of traditional chemical polishing liquids containing harmful chemical substances, thereby greatly reducing environmental pollution during the polishing process and protecting the health of operators. In addition, the present disclosure has significant advantages in terms of cost. The configuration cost of the artificial leather polishing cloth and the environmentally friendly solvent is much lower than that of traditional chemical polishing liquids, which not only reduces production costs but also reduces the dependence on safety measures, making the overall process more economical and practical.
[0033] Figure 1 The flowchart of the surface polishing method for perovskite crystal materials according to an embodiment of the present disclosure is schematically shown.
[0034] Refer to Figure 1 , the surface polishing method 100 of the perovskite crystal material in this embodiment includes operations S110 to S130.
[0035] In operation S110, perform hot mounting treatment on a perovskite single crystal to be polished to obtain a perovskite single crystal sample.
[0036] In an embodiment of the present disclosure, paraffin wax can be used as the hot embedding material in the hot embedding process. Specifically, paraffin wax can be heated to melt it, and the perovskite single crystal sample can be immersed in the molten paraffin wax; after cooling, the paraffin wax solidifies and wraps the perovskite single crystal sample to form a stable support structure. By wrapping with paraffin wax, the perovskite single crystal sample can be effectively fixed, avoiding cracking or deformation of the sample caused by unstable or uneven stress during the subsequent polishing process, and helping to maintain the integrity of the crystal.
[0037] In an embodiment of the present disclosure, the size of the perovskite single crystal sample should be adapted to the size of the fixing table of the polishing table. Exemplarily, the diameter of the formed cylindrical paraffin wax sample can be in the range of less than 25 mm and the height is less than 30 mm.
[0038] It should be noted that the polishing methods in the prior art generally use cold embedding. Although this process can fix the crystal sample, it may cause the sample to be fixed unstably, thereby increasing the instability during the processing, especially during high-precision polishing. Through the hot embedding process of the present disclosure, paraffin wax is used to wrap the perovskite single crystal sample to ensure that the sample can be stably fixed on the polishing table, avoiding the problem of unstable fixation brought by the cold embedding method.
[0039] In operation S120, the perovskite single crystal sample is fixed to the polishing table, and rough grinding and polishing are performed on the perovskite single crystal sample.
[0040] The polishing table finely processes the surface of the sample through rotation and friction to achieve a smooth and flat effect. The polishing table can adjust the rotation speed, pressure, and polishing time of the turntable according to different process requirements to ensure the uniformity and accuracy of surface treatment: by controlling the rotation speed, the polishing table can affect the polishing rate, thereby realizing different stages of rough grinding or fine grinding; pressure control helps to adjust the polishing intensity to ensure that an appropriate pressure is applied to the surface of the sample to avoid excessive wear or insufficient polishing.
[0041] The polishing table generally consists of an upper turntable, a lower turntable, a drive system, and an adjustment system. The upper turntable is used to fix the sample to be polished, and the adjustment of its rotation speed and pressure has a greater impact on the polishing effect. The lower turntable provides the frictional force required for polishing through the relative movement with the upper turntable, and is usually also equipped with an independent rotation speed adjustment function to adapt to different polishing requirements. The drive system drives the rotation of the upper and lower turntables through a motor to ensure the stable rotation of the turntables, and provides different operating speeds through the adjustable speed function to meet the requirements of different polishing stages such as rough grinding and fine grinding. The adjustment system is used to adjust parameters such as polishing pressure, turntable speed, and time to optimize the polishing process and ensure the surface treatment effect of different materials.
[0042] According to an embodiment of the present disclosure, during the rough grinding process, silicon carbide sandpaper with mesh numbers ranging from 300-500 mesh, 700-900 mesh, 1000-1300 mesh and 1800-2200 mesh can be selected, and rough grinding and polishing can be performed in sequence. Each mesh number of sandpaper corresponds to a different polishing stage, starting with coarser sandpaper, and gradually using finer sandpaper for refinement to ensure that the surface is gradually flat and smooth. During the rough grinding and polishing process, the sample is fixed on the polishing table, and the fixing pressure can be set to 0.1-0.2MPa to ensure that the contact force between the sample and the sandpaper is appropriate during polishing to avoid excessive wear or damage to the sample surface. The upper turntable speed of the polishing table can be set to 40-60rpm, while the lower turntable speed can be set between 70-90rpm to ensure a uniform polishing effect. The polishing time of each stage can be set to 2-5min according to the mesh number of the sandpaper to meet the polishing requirements of sandpapers with different mesh numbers.
[0043] In the embodiments of the present disclosure, silicon carbide sandpaper has strong hardness and sharpness, and is suitable for processing materials with higher hardness. Its main component is silicon carbide, which is second only to diamond in hardness, so it can effectively remove irregularities and rough parts of the surface. Silicon carbide sandpaper ranges from coarse sandpaper to fine sandpaper. The smaller the mesh number, the coarser the particles, and the stronger the grinding force, which is suitable for removing larger defects; while sandpaper with a larger mesh number is used for fine polishing and improving surface finish.
[0044] Furthermore, in the process of rough grinding and polishing, in order to ensure the polishing accuracy and surface quality, anhydrous ethanol can be dripped into the contact area between the polishing surface and the sandpaper at a uniform flow rate throughout the process to perform a third dripping treatment. The purpose of the third dripping treatment is to allow an appropriate amount of anhydrous ethanol to flow into the polishing area to take away the grinding heat and abrasive particles, help clean and lubricate the polishing surface, reduce the heat accumulation caused by friction during the polishing process, and prevent the accumulation of particles and impurities, thereby optimizing the rough grinding effect.
[0045] Exemplarily, the flow rate of the third dripping treatment can be set to 8-20 mL / min. For example, the flow rate of the third dripping treatment can be set to 10 mL / min to ensure that the dripped anhydrous ethanol can slowly penetrate during the treatment process, continuously maintain a proper lubrication state, and prevent excessive friction and surface overheating.
[0046] In operation S130, the coarsely ground perovskite single crystal sample is finely ground and polished to obtain a polished perovskite single crystal sample, wherein the fine grinding and polishing process includes: using an artificial leather polishing cloth and performing a first dropwise addition treatment with anhydrous ethanol as a polishing liquid; after a preset time interval of the first dropwise addition treatment, the anhydrous ethanol is replaced with a suspension of dimethyl sulfoxide and anhydrous ethanol, and a second dropwise addition treatment is performed on the finely ground perovskite single crystal sample.
[0047] In an embodiment of the present disclosure, after the rough grinding and polishing process is completed, the fine grinding and polishing stage is entered. In order to further improve the smoothness and uniformity of the sample surface, the coarse sandpaper on the lower turntable of the polishing table can be replaced with an artificial leather polishing cloth.
[0048] Specifically, an artificial leather polishing cloth with a fiber diameter less than 1 µm can be used. The tiny fibers can better contact the sample surface, and since they do not contact solid particles, abrasive wear on the sample surface is reduced, minimizing scratches. Compared with traditional polishing cloths with larger roughness, the tiny fibers can apply uniform pressure on the crystal surface during the polishing process, reducing local wear, effectively reducing the roughness of the sample surface, helping the sample surface reach the nanoscale smoothness, making the surface state of the sample smoother and more uniform, improving the surface quality, reducing potential microcracks and defects, and contributing to enhancing the optoelectronic performance of the crystal.
[0049] Furthermore, the components in the artificial leather polishing cloth can include polyurethane resin and viscose fiber to have good elasticity and toughness, effectively meeting the requirements for fine surface treatment during the fine grinding process.
[0050] During the fine grinding and polishing process, the fixed pressure of the sample can be set to 0.3 - 0.4 MPa. This pressure range ensures sufficient contact force between the polishing cloth and the sample surface, thus ensuring a fine polishing effect, while not damaging the sample surface due to excessive pressure. The rotational speed of the upper turntable of the polishing table can be set to 40 - 60 rpm to ensure that the polishing cloth can uniformly contact the sample surface and continuously perform polishing, while avoiding excessive friction or uneven surface caused by too fast a rotational speed. The rotational speed of the lower turntable can be set to 80 - 150 rpm, which helps to increase the rotation trajectory of the sample on the polishing cloth, further ensuring the uniformity and stability of the fine grinding and polishing.
[0051] Meanwhile, during the fine grinding and polishing process, anhydrous ethanol can be used as the polishing liquid for the first dripping treatment. Similar to the third dripping treatment, anhydrous ethanol has good lubricity and cleaning properties, which can effectively reduce friction and heat generation during the polishing process, maintaining the smoothness and uniformity of the sample surface. Moreover, the first dripping treatment can also help remove tiny particles generated during the polishing process, preventing these particles from affecting the polishing effect or causing secondary scratches on the sample surface. The flow rate and preset time interval of the first dripping treatment can be adjusted according to the process requirements to ensure that anhydrous ethanol can uniformly penetrate between the sample and the polishing cloth, maintaining a continuous lubrication effect, reducing surface scratches and particle accumulation.
[0052] Exemplarily, the flow rate of the first dropping process can be set to 10 - 30 mL / min. For example, the flow rate of the first dropping process can be set to 20 mL / min to ensure that the lubricating fluid used in the polishing process can be evenly and stably distributed between the sample surface and the polishing cloth. The preset time interval of the first dropping process can be set to 20 - 40 min, so as to ensure that the polishing fluid uniformly penetrates and continuously plays a role during the entire polishing process, so that the polishing process in each stage can maintain stable conditions.
[0053] Further, after a preset time interval, the first dropping process is completed, and anhydrous ethanol can be replaced with a suspension of dimethyl sulfoxide (DMSO) and anhydrous ethanol for the second dropping process.
[0054] In the embodiments of the present disclosure, using a suspension composed of DMSO and anhydrous ethanol as the polishing fluid gives the present disclosure more unique advantages. Ethanol and dimethyl sulfoxide each have specific chemical properties and dissolution capabilities, and their combination can play a synergistic role in the fine grinding and polishing process, effectively solving various challenges in crystal surface treatment.
[0055] Specifically, anhydrous ethanol is a widely used organic solvent with strong dissolution ability, especially effective in dissolving organic impurities. It can not only remove tiny organic pollutants on the crystal surface, but also effectively dissolve some insoluble substances on the crystal surface, thus avoiding uneven polishing or incomplete polishing caused by surface impurities. Due to the strong volatility of ethanol, it can quickly evaporate during use and will not cause long-term corrosion to the crystal. Therefore, ethanol can provide necessary lubrication and cleaning functions during the fine grinding process, helping to improve the polishing effect and protect the crystal surface.
[0056] On the other hand, DMSO is a polar solvent with extremely strong dissolution ability. Especially when mixed with water or other solvents, it can enhance the ability to dissolve other chemical substances. Adding DMSO to the suspension can utilize its excellent polarity and dissolution ability to remove those impurities that are difficult to remove on the crystal surface, especially metal oxides or other harmful substances. More importantly, DMSO has a chemical passivation effect. It can form a thin film on the crystal surface, and this passivation film can reduce the defects on the crystal surface, lower the dark current caused by surface activity, and thus improve the electrical stability of the crystal. Therefore, adding the specific chemical substance DMSO to the suspension can not only achieve polishing, but also passivate the crystal surface during this process, reduce surface defects, further improve the optoelectronic properties of the crystal surface, and effectively extend the service life of optoelectronic devices.
[0057] In an embodiment of the present disclosure, for the suspension prepared from DMSO and absolute ethanol, absolute ethanol plays a role in dissolving and removing impurities that may be generated during the chemical passivation process of DMSO, ensuring that the impurities in the passivation solution are removed in a timely manner and maintaining the surface state of the sample at a high-quality level at the end of fine polishing. Due to the characteristics of absolute ethanol to quickly dissolve and remove impurities, it can effectively avoid the generation of unnecessary residues during the passivation process, thereby ensuring the stability and uniformity of the surface passivation film. Therefore, through the polishing treatment steps that combine absolute ethanol and dimethyl sulfoxide, the present disclosure can achieve surface passivation while polishing to maintain the high quality of the crystal surface and avoid problems such as surface non-uniformity or chemical instability that may occur in the traditional passivation process.
[0058] In an embodiment of the present disclosure, in the suspension of dimethyl sulfoxide and absolute ethanol, the volume ratio of dimethyl sulfoxide to absolute ethanol can be 1:1 - 3:1.
[0059] Furthermore, through multiple experiments, the applicant found that when preparing the suspension with ethanol and DMSO at a volume ratio of 1:1, the advantages of both can be fully complemented and exerted. Specifically, it can ensure that the suspension has sufficient cleanliness and avoid excessive corrosion or damage to the crystal surface. The chemical passivation effect of DMSO and the physical lubrication effect of ethanol complement each other, ensuring the uniformity and stability of the crystal surface during the polishing process, thereby minimizing surface defects and loss of crystal performance while ensuring the polishing effect.
[0060] Therefore, another major advantage of the present disclosure is its simple operation. By integrating the polishing and passivation processes, the traditional process flow is simplified. In the traditional process, the polishing and passivation processes usually need to be carried out separately, increasing the process complexity and production time. The integrated design of polishing and passivation in the present disclosure not only simplifies the process flow but also improves the production efficiency.
[0061] Exemplarily, the flow rate of the second dropping treatment can be set to 8 - 20 mL / min, preferably 10 mL / min, and the time of the second dropping treatment can be set to 4 - 7 min.
[0062] In an embodiment of the present disclosure, the absolute ethanol used in the rough grinding and fine grinding processes can be selected with a purity of greater than or equal to 99.99%. High-purity ethanol does not contain moisture and impurities, so when dissolving organic impurities, particles or pollutants on the crystal surface, it will not introduce any additional moisture or harmful substances, avoiding reactions that may have an adverse effect on the crystal surface.
[0063] Furthermore, using high-purity anhydrous ethanol as the polishing liquid can ensure that there is almost no moisture or impurities in the liquid, avoiding chemical reactions and corrosion problems caused by moisture. At the same time, the volatility of anhydrous ethanol enables it to evaporate rapidly during the polishing process, avoiding uneven effects caused by liquid residue on the sample surface. Through the rapid evaporation of anhydrous ethanol, it can effectively carry away the heat generated during the polishing process, preventing the sample from thermal deformation or cracking due to overheating. Especially when processing perovskite samples with greater brittleness, this characteristic is particularly important. The brittleness of perovskite materials makes them vulnerable to thermal stress in traditional polishing methods, resulting in cracks or damage, while the present disclosure effectively avoids this problem through the volatility of anhydrous ethanol.
[0064] According to the embodiments of the present disclosure, by using high-purity anhydrous ethanol as the polishing liquid, the introduction of moisture and impurities can be effectively avoided, and the corrosive effects that may be brought by traditional polishing liquids can be avoided. The volatility of anhydrous ethanol enables it to evaporate rapidly during the polishing process, timely carrying away the heat generated by the friction between the sample and the polishing cloth, effectively preventing thermal deformation and cracks on the sample surface caused by overheating, thereby improving the integrity and stability of the sample. Secondly, using an artificial fiber polishing cloth with a fiber diameter less than 1 µm can provide a more uniform polishing effect, avoiding scratches and uneven wear caused by traditional larger particles. The fine polishing cloth effectively reduces the surface roughness of the sample, ultimately achieving a nanoscale smooth effect, improving the surface quality of the sample, and providing a high-quality surface basis for subsequent optoelectronic performance tests. In the fine polishing treatment step, the present disclosure further optimizes the surface state of the sample by using a combined suspension of anhydrous ethanol and dimethyl sulfoxide. Anhydrous ethanol can effectively remove the impurities generated during the passivation process of dimethyl sulfoxide in this process, ensuring that the formation of the passivation film is more uniform and stable, thereby improving the electrical stability of the sample. The passivation treatment of dimethyl sulfoxide helps to reduce the defects on the crystal surface, prevent non-radiative recombination, and significantly improve the optoelectronic performance of the sample.
[0065] In the embodiments of the present disclosure, the above method can be used to process perovskite crystal materials to obtain perovskite crystal materials with excellent surface smoothness, low roughness, and better optoelectronic performance.
[0066] Next, the implementation manners of the present disclosure will be elaborated through multiple embodiments. However, those skilled in the art should be aware that these embodiments are only for explaining the present disclosure and do not limit the scope of the present disclosure. Those skilled in the art can draw on the content of this article and appropriately modify the process parameters to achieve. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in this application. As for the reagents or equipment without specifying the brand or manufacturer, they are all standard products that can be easily obtained on the market.
[0067] Example 1
[0068] The paraffin sample containing cesium lead bromide single crystal was installed in the sample fixing hole of the polishing table, and the sample fixing pressure was set to 0.1 - 0.2 MPa. Then, 400-mesh, 800-mesh, 1200-mesh, and 2000-mesh silicon carbide sandpapers were selected to rough grind the sample in sequence to remove the cutting marks introduced by wire cutting on the surface of the cesium lead bromide crystal. The rough grinding time for sandpapers of different mesh numbers was set to 3 minutes, and throughout the process, anhydrous ethanol was dropped at a flow rate of 10 mL / min to carry away the heat and particles generated during grinding, ensuring the stability of the polishing effect. The rotational speed of the upper turntable of the polishing table was set to 50 rpm, and the rotational speed of the lower turntable was set to 80 rpm to ensure the uniformity and effectiveness during the grinding process.
[0069] Example 2
[0070] Based on Example 1, the rough sandpaper on the lower turntable of the polishing table was replaced with artificial leather polishing cloth with a fiber diameter less than 1 µm, and the sample was started to be finely ground and polished. The sample fixing pressure was set to 0.3 - 0.4 MPa to ensure full contact between the polishing cloth and the sample surface. The dropping speed of anhydrous ethanol was set to 20 mL / min to continuously carry away the heat and particles generated during polishing. The rotational speed of the upper turntable of the polishing table was set to 50 rpm, and the rotational speed of the lower turntable was set between 80 - 150 rpm to ensure the uniformity and stability during the polishing process. The total time of the first dropping treatment of adding anhydrous ethanol was set to 30 min to ensure that the surface treatment reached the ideal flatness and smoothness.
[0071] Example 3
[0072] A suspension was prepared according to the volume ratio of dimethyl sulfoxide to anhydrous ethanol of 1:1. The anhydrous ethanol in the process of Example 2 was replaced with the prepared suspension, and the sample was further processed. The sample fixing pressure was set to 0.3 - 0.4 MPa, the dropping speed of the suspension was set to 10 mL / min, the rotational speed of the upper turntable was set to 50 rpm, and the rotational speed of the lower turntable was adjusted between 80 - 150 rpm to ensure uniform polishing. The time of the second dropping treatment of adding the suspension was set to 5 min to ensure the effective formation of the passivation effect.
[0073] Example 4
[0074] The optoelectronic properties of the cesium lead bromide perovskite single crystal sample after the rough grinding, fine grinding, and polishing treatments of Examples 1 - 3 were tested to verify the changes in its detection performance. Among them, the test contents included the dark current, laser response, and surface roughness of the crystal, and the improvement of these parameters could directly reflect the improvement of the crystal surface quality.
[0075] Figure 2 Shows a comparison chart of the sample morphology and transparency before and after polishing according to an embodiment of the present disclosure. As Figure 2 shown, the obvious grid background is used as an auxiliary tool for comparative analysis. The sample before polishing (left) has relatively rough or irregular textures, resulting in low smoothness and low transparency of the overall sample; while the crystal after polishing according to Embodiments 1-3 of the present disclosure (right) has a smoother surface, with almost no obvious roughness, and the transparency of the sample has been improved, and a clear grid background can be presented.
[0076] The improvement in transparency indicates that the polishing process removes some microscopic defects and irregular structures on the surface, thereby enhancing the light transmission ability. The uniformity of the sample surface has also been significantly improved, and the visual effect has become more uniform.
[0077] Figure 3 Schematically shows a chart of the perovskite crystal roughness test results of the sample before and after polishing according to an embodiment of the present disclosure. Specifically, an atomic force microscope (AFM) is used to test the roughness of the sample before and after polishing. The roughness of the perovskite sample before polishing (left) is 0.09 µm, while the roughness of the sample after polishing (right) drops to 0.89 nm. It can be seen that by using the surface polishing method of Embodiments 1-3 of the present disclosure, the surface roughness of the perovskite crystal has decreased by more than 100 times.
[0078] Furthermore, I-V characteristic tests and laser response tests are carried out on the samples before polishing, after polishing and after surface passivation. The laser used is a purple laser with a power of 27 µW and a wavelength of 405 nm, and the laser irradiates from a position 5 cm away from the side of the sample. Metal electrodes of 100 nm thick gold (Au) and indium (In) are respectively evaporated on the upper and lower surfaces of the test sample to ensure good electrical contact and facilitate signal extraction.
[0079] Figures 4A to 4C Schematically shows the I-V curve and laser response result chart of the sample before and after polishing according to an embodiment of the present disclosure. Figure 4A is the I-V curve of the unpolished sample. The dark current is 9.8 µA under a bias voltage of 100 V. Due to the large dark current, the signal generated by the laser is submerged, resulting in no response when the laser irradiates the sample; Figure 4B is the I-V curve and laser response of the sample after the first dropwise treatment. The dark current of the sample after the first dropwise treatment is 0.1 nA under a bias voltage of 100 V, indicating that this treatment process significantly reduces the dark current of the sample, and the reduction amplitude reaches 4 orders of magnitude. And the maximum laser response of this sample is 2.7×10 3 times; Figure 4CI-V curves and laser responses of the sample after the second dropwise addition treatment. It can be seen that the process after the second dropwise addition treatment in the present disclosure can annihilate the Pb dangling bonds on the surface of the sample, enabling the sample to form an ohmic contact with the metal electrode. Under the bias conditions of +100 V and -100 V, the laser responses are 5.2×10 3 times and 5.7×10 3 times, respectively.
[0080] The embodiments of the present disclosure have been described above. However, these embodiments are for illustrative purposes only and not for limiting the scope of the present disclosure. Although the embodiments have been described separately above, this does not mean that the measures in the embodiments cannot be used advantageously in combination. Without departing from the scope of the present disclosure, those skilled in the art can make various substitutions and modifications, and these substitutions and modifications should fall within the scope of the present disclosure.
Claims
1. A method for surface polishing of a perovskite crystal material, characterized in that, The method includes: Performing hot embedding treatment on the perovskite single crystal to be polished to obtain a perovskite single crystal sample; Fixing the perovskite single crystal sample on a polishing table and performing rough grinding and polishing on the perovskite single crystal sample; and Performing fine grinding and polishing on the rough-ground perovskite single crystal sample to obtain a polished perovskite single crystal sample, wherein the process of fine grinding and polishing includes: using an artificial leather polishing cloth and performing a first dropwise addition treatment with absolute ethanol as a polishing liquid; after a preset time interval has passed since the first dropwise addition treatment, replacing the absolute ethanol with a suspension of dimethyl sulfoxide and absolute ethanol for a second dropwise addition treatment.
2. The method according to claim 1, wherein In the suspension of dimethyl sulfoxide and absolute ethanol, the volume ratio of dimethyl sulfoxide to absolute ethanol is 1:1 - 3:
1.
3. The method according to claim 1, wherein The hot embedding treatment specifically includes: using paraffin to perform hot embedding on the perovskite single crystal to be polished to obtain the perovskite single crystal sample, wherein the size of the perovskite single crystal sample obtained by hot embedding is adapted to the size of the sample fixing table in the polishing table.
4. The method according to claim 1, wherein Successively performing rough grinding and polishing on the perovskite single crystal sample with silicon carbide sandpapers having a mesh number range of 300 - 500 mesh, 700 - 900 mesh, 1000 - 1300 mesh, and 1800 - 2200 mesh.
5. The method according to claim 4, wherein The sample fixing pressure during the rough grinding and polishing process is set to 0.1 - 0.2 MPa, the rotation speed of the upper turntable on the polishing table is set to 40 - 60 rpm, the rotation speed of the lower turntable on the polishing table is set to 70 - 90 rpm, and the rough grinding and polishing time for silicon carbide sandpapers of different mesh numbers is set to 2 - 5 min.
6. The method according to claim 4, wherein During the rough grinding and polishing process, a third dropwise addition treatment is performed with absolute ethanol, and the flow rate of the third dropwise addition treatment is set to 8 - 20 mL / min.
7. The method according to any one of claims 4 to 6, characterized in that After the rough grinding process is completed, the silicon carbide sandpaper is replaced with an artificial leather polishing cloth, and the fiber diameter of the artificial leather polishing cloth is less than 1 µm.
8. The method according to claim 7, characterized in that, The artificial leather polishing cloth is composed of polyurethane resin and viscose fiber.
9. The method according to claim 1 or 7, characterized in that, The sample fixing pressure during the fine grinding and polishing process is set to 0.3 - 0.4 MPa, the flow rate of the first dropwise addition treatment is set to 10 - 30 mL / min, the rotation speed of the upper turntable on the polishing table is set to 40 - 60 rpm, the rotation speed of the lower turntable on the polishing table is set to 80 - 150 rpm, and the preset time interval of the first dropwise addition treatment is set to 20 - 40 min.
10. The method according to claim 1, wherein The flow rate of the second dropwise addition treatment is set to 8 - 20 mL / min, the rotation speed of the upper turntable on the polishing table is set to 40 - 60 rpm, the rotation speed of the lower turntable on the polishing table is set to 80 - 150 rpm, and the time of the second dropwise addition treatment is set to 4 - 7 min.
11. The method according to claim 1 or 6, characterized in that, The purity of the absolute ethanol is greater than or equal to 99.99%.
12. A perovskite crystal, characterized in that, The perovskite crystal is surface-treated by using the surface polishing method of the perovskite crystal material according to any one of claims 1 - 11.
Citation Information
Patent Citations
Perovskite single crystal polishing method and application thereof
CN117794341A
Method for manufacturing super-flat polycrystalline diamond film on large scale
CN119465395A
Perovskite compositions comprising mixed solvent systems
EP3775065A1
Method for preparing nanosized mixed crystal of cyanuric acid coated halide perovskite and use thereof
US20250102861A1
Cited By
Halide perovskite single crystal and surface polishing method thereof
CN122142883A